Tunable laser generation with erbium-doped microfiber knot resonator - Sulaiman, Azlan; Harun, Sulaiman Wadi; Ahmad, Fauzan; Norizan, Siti Fatimah; Ahmad, Harith (IOP Publishing, 2012)
A tunable laser is demonstrated using a microfiber knot resonator structure made by erbiumdoped fiber (EDF). The laser is made of a 2 m long EDF where 30 mm of its end section is tapered to construct a microfiber knot resonator (MKR). The combination of the EDF and MKR generates a stable single wavelength laser at 1555 nm wavelength with a signal to noise ratio (SNR) of 33.7 dB using a 63 mW of 980 nm pump power. The peak wavelength of the laser can be tuned by 340 pm as the MKR diameter reduces from 5.0 to 0.5 mm with an acceptable penalty in output power.